Atomic structure of an FeCrMoCBY metallic glass revealed by high energy x-ray diffraction. (13th July 2022) - Pussi, K; Louzguine-Luzgin, D V; Nokelaineni, J; Barbiellini, B; Kothalawala, V; Ohara, K; Yamada, H; Bansil, A; Kamali, S
Abstract: Amorphous bulk metallic glasses with the composition Fe48 Cr15 Mo14 C15 B6 Y2 have been of interest due to their special mechanical and electronic properties, including corrosion resistance, high yield-strength, large elasticity, catalytic performance, and soft ferromagnetism. Here, we apply a reverse Monte Carlo technique to unravel the atomic structure of these glasses. The pair-distribution functions for various atomic pairs are computed based on the high-energy x-ray diffraction data we have taken from an amorphous sample. Monte Carlo cycles are used to move the atomic positions until the model reproduces the experimental pair-distribution function. The resulting fitted model is consistent with our ab initio simulations of the metallic glass. Our study contributes to the understanding of functional properties of Fe-based bulk metallic glasses driven by disorder effects.